"Of course we have criteria" Assessment criteria as material semiotic means in face-to-face assessment interaction. (March 2020) - Meyer-Beining, Janna; ,
Abstract: Assessment criteria and grading rubrics have received much attention in terms of their ability to support teachers' grading and students' learning processes in higher education. This study addresses an underexplored aspect of the institutional use of assessment criteria and explores their function as communicative resources in assessment delivery. The study is based on a small corpus of video-recorded grade delivery meetings in Swedish higher education. Using interaction analysis, the study aimed to uncover how participants used an institutional criteria sheet as a means to support their collaborative communicative work of delivering and receiving a grade on student writing. Three main functions of the criteria sheet were determined. First, the list of criteria inscribed on the sheet provided structure to a meeting that lacked a formal agenda. Second, the list of criteria was used as a mnemonic device, connecting grade delivery to teachers' original grading efforts. Third, the criteria sheet was used as an analogous abstraction of the report, providing spatial orientation for complex discussions of student writing. The paper argues that assessment criteria, when used in assessment delivery, may provide useful support for participants' efforts to achieve the joint task of grade delivery.